Toward hyperpolarized molecular imaging of HIV: synthesis and longitudinal relaxation properties of 15N‐Azidothymidine. (25th August 2014) - Shchepin, Roman V.; Chekmenev, Eduard Y.
<x xml:space="preserve">Abstract</x> Previously unreported 15N labeled Azidothymidine (AZT) was prepared as an equimolar mixture of two isotopomers: 1‐15N‐AZT and 3‐15N‐AZT. Polarization decay of 15N NMR signal was studied in high (9.4 T) and low ( 50 mT) magnetic fields. 15N T1 values were 45 ± 5 s (1‐15N‐AZT) and 37 ± 2 s (3‐15N‐AZT) at 9.4 T, and 140 ± 16 s (3‐15N‐AZT) at 50 mT. 15N‐AZT can be potentially 15N hyperpolarized by several methods. These sufficiently long 15N‐AZT T1 values potentially enable hyperpolarized in vivo imaging of 15N‐AZT, because of the known favorable efficient (i.e., of the time scale shorter than the longest reported here 15N T1) kinetics of uptake of injected AZT. Therefore, 3‐15N‐AZT can be potentially used for HIV molecular imaging using hyperpolarized magnetic resonance imaging.